KEEFEKTIFAN PENDEKATAN BEHAVIOR MENGGUNAKAN TEKNIK TOKEN ECONOMY UNTUK MENINGKATKAN ATENSI BELAJAR SISWA KELAS VIII DI SMP N 29 SEMARANG - Ajeng Setyani; Mulawarman Mulawarman (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2020)
This study aims (1) to identify and analyze students' attentiveness levels of learning before getting a behavioral approach using token economy techniques, (2) identifying and analyzing learning attentions when getting behavioral approaches using token economy techniques, and (3) analyzing the effectiveness of behavior approaches using token economy techniques in increasing student attention in class VIII at SMP N 29 Semarang. This research is an experimental research with one group pretest-posttest design. Data collection techniques used were psychological scales with a learning attention instrument of 35 items. The population in this study were students of class VIII at SMP N 29 Semarang with a total sample of 5 students who were determined purposively. Data analysis techniques used (1) quantitative descriptive analysis to describe the level of student learning attention, (2) hypothesis testing with Wilcoxon analysis to determine the effect of the behavior approach using token economy techniques. The results showed that the behavioral approach using token economy techniques had an effect on increasing student attention